Pembinaan Kerohanian Anak Sekolah Minggu Melalui Panggung Boneka di GKJ Wiladeg Gunungkidul Yogyakarta - Sri Dwi Harti; Amellia Ardaning Sandrawati; Ardison Nenoliu; Marta Klarita Lessa; Gita Amanda; Ince Selan; Yenni Kasse (Vieka Wahana Semesta, 2025)
Abstract The spiritual development of Sunday School children is an important foundation in the development of their faith, character, and personal relationship with God from an early age. This development process places Sunday School teachers as central figures, not only as teachers, but also as spiritual role models who reflect the love and integrity of Christ in their daily lives. The consistency of the teachers' spiritual lives serves as a tangible example for children in living out biblical values. In addition, effective nurturing requires synergy between the church and the family. Parents have an important role in reinforcing faith practices such as prayer, Bible reading, and acts of love at home, which complement the lessons children receive at church. At GKJ Wiladeg, there are challenges in the spiritual development of children because conventional teaching methods are not very interesting, resulting in low enthusiasm and understanding of God's word among children. Sunday School teachers also find it difficult to convey biblical values in a contextual and interesting way. In facing the challenges of the times, innovative teaching methods such as the use of puppet stages have proven effective in conveying Bible stories by engaging children's visual, auditory, and emotional aspects. This multisensory approach allows children to more easily understand, remember, and apply God's word in their daily lives. Through this comprehensive approach, Sunday School spiritual development is expected to produce a generation that knows God, loves Him, and lives as witnesses of Christ in the world. Abstrak Pembinaan kerohanian anak Sekolah Minggu merupakan fondasi penting dalam pengembangan iman, karakter, dan hubungan pribadi anak dengan Tuhan sejak dini. Proses pembinaan ini menempatkan guru Sekolah Minggu sebagai tokoh sentral, tidak hanya sebagai pengajar, tetapi juga sebagai teladan rohani yang mencerminkan kasih dan integritas Kristus dalam kehidupan sehari-hari. Konsistensi kehidupan rohani guru menjadi contoh nyata bagi anak dalam menghidupi nilai-nilai Alkitab. Selain itu, pembinaan yang efektif memerlukan sinergi antara gereja dan keluarga. Orang tua memiliki peran penting dalam memperkuat pembiasaan iman seperti doa, pembacaan Alkitab, dan perbuatan kasih di rumah, yang melengkapi pembelajaran yang diterima anak di gereja. Di GKJ Wiladeg terdapat tantangan dalam pembinaan kerohanian anak karena metode pengajaran yang konvensional kurang menarik, sehinga antusiasme dan pemahaman anak terhadap firman Tuhan rendah. Guru Sekolah Minggu juga kesulitan menyampaikan nilai-nilai Alkitab secara kontekstual dan menarik. Dalam menghadapi tantangan zaman, inovasi metode pembinaan seperti penggunaan panggung boneka terbukti efektif dalam menyampaikan cerita Alkitab dengan melibatkan aspek visual, auditori, dan emosional anak. Pendekatan multisensori ini memungkinkan anak lebih mudah memahami, mengingat, dan menerapkan firman Tuhan dalam kehidupan sehari-hari. Melalui pendekatan yang menyeluruh ini, pembinaan kerohanian Sekolah Minggu diharapkan mampu menghasilkan generasi yang mengenal Tuhan, mengasihi-Nya, dan hidup sebagai saksi Kristus di tengah dunia.